Molecular response of a patient with e19a2-positive chronic myeloid leukemia to flumatinib: a case report and literature review - Feng, Yaqing; Wang, Hongjin; Zhang, Lidong; Gong, Jinying; Liu, Xi; Mu, Caiqin; Qiao, Jun; Meng, Haitao; Zhang, Yanfang (Frontiers in Medicine, 2025)
ObjectiveChronic myeloid leukemia (CML) is a malignancy driven by the BCR::ABL1fusion gene, with the e19a2 transcript being a rare variant, accounting for 0.4% of CML cases. Patients with the e19a2 transcript often show poor response to first-line treatment with imatinib, and no standard therapy has been established for this subtype.MethodsWe report a case of a 28-year-old female with e19a2-positive CML. The patient exhibited poor response and tolerance to dasatinib. After 6 months, she achieved partial cytogenetic response (PCyR) but developed grade 3 pleural effusion. Following treatment discontinuation and prednisone therapy, the patient continued dasatinib (80 mg/d). At 12 months, the patient achieved complete cytogenetic response (CCyR), but BCR::ABL1 levels remained suboptimal, with recurrent pleural effusion. The patient was then switched to flumatinib (600 mg/d), achieving major molecular response (MMR) at 6 months and deep complete molecular response (MR4.5) at 24 months, with good tolerance.ConclusionFlumatinib demonstrated excellent deep molecular response and good tolerability in e19a2-positive CML patients, suggesting that it may be one of the preferred treatment options for such patients.